Transforming Sembalun Tourism Village: Institutional Reorganization to Boost Local Capacity and Sustainable Tourism in Sembalun - Arief Rahman; Nida Farah; Hana Putri (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Rural tourism development has emerged as a vital pathway for fostering economic resilience, preserving cultural heritage, and enhancing community welfare. This study examines the institutional reorganization process in Sembalun Tourism Village and its role in strengthening local capacity for sustainable tourism development. Sembalun, located in East Lombok, Indonesia, possesses rich natural and cultural assets but faces governance and coordination challenges that limit its full potential. Utilizing a mixed methods approach, the research integrates qualitative interviews with local stakeholders and quantitative assessments of institutional performance indicators before and after reorganization efforts. The results indicate that institutional restructuring, including clearer governance roles, capacity building for village organizations, and collaborative planning mechanisms, significantly improved community participation, service quality, and tourism management effectiveness. Local stakeholders reported increased confidence in decision making and stronger market competitiveness. The study also highlights the importance of aligning institutional frameworks with sustainable tourism principles to balance economic growth with environmental stewardship. Findings suggest that participatory institutional reforms can empower rural communities, enhance tourism sustainability, and serve as a model for other emerging tourism villages in Indonesia. This research contributes to rural tourism governance literature and provides practical insights for policymakers and practitioners striving to achieve community led sustainable tourism.